The secret of moon castle - Blyton, Enid; Wynne, Dudley (Award Publications Worksop, Nottinghamshire, 2009)
When Mike, Nora, Peggy and Jack go on holiday with Prince Paul and stay at the remote Moon Castle, they are excited to discover its mysterious past. They soon find that weird things still happen there - paintings come alive, books fly off shelves and abandoned tin mines light up with a strange glow. Can the friends solve the mysteries of Moon Castle?